The Demand of Heterogeneous Labour in Germany - Martin Falk; Bertrand M. Koebel (Zentrum für Europäische Wirtschaftsforschung (ZEW); ZBW – Leibniz Information Centre for Economics, 1997)
In this paper, four commonly provided explanations for the shift in labour demand for different skill groups are investigated: the substitutability of inputs; the own-price sensitivity for different types of labour; the effect of economic growth and the impact of technological change. In general, the shift of demand away from unskilled labour can be explained by the large own-price elasticity of unskilled labour and by biased technological change. During the period of 19771994, the rate of biased technological progress against unskilled workers seems to be as large in the traded as in the non-traded goods industries. Furthermore, in three out of five sectors considered, technological change is biased towards high-skilled labour.
Keywords: D24; J23; O33; 330; technological change; heterogeneous labour